Identification of Student Misconceptions Using Four Tier Diagnostic Instruments On Straight Motion Materials - Erlangga, Sony Yunior; Winingsih, Puji Hariati; Saputro, Handoyo (COMPTON Jurnal Ilmiah Pendidikan Fisika, 2022)
This study aims to identify the quantity of students who misconceptions on the material of Straight Motion. The research subjects were 30 students of class X MIA 1 of Yogyakarta SahabatQu High School with purposive sampling technique. This type of research is a quantitative descriptive study with data collection techniques carried out by triangulation namely documentation of test results, interviews and questionnaires. The research instrument used was a three-tier test. the results of the most frequent misconception sequences were found in vertical motion (26%), speed and speed (18%), GLB (17%), distance and displacement (16%), and GLBB (15%). Based on the results of the interview showed the same thing.